Textfiguren als linguistischer Analysegegenstand der Ratgeberforschung - Niemann, Robert (2022)
This paper seeks to apply the concepts of authorship and the authorial figure, as used in the research of scientific writing, to the investigation of advice literature. It reflects on advantages and disadvantages of these concepts in terms of methodology. In doing so, previous research will be challenged by offering an approach focusing on the textual analysis of figures in advice texts.
Keywords: authorship; authorial figure; advice literature